Ballistic gelatin calibration standardisation. Issue 2 (12th March 2020) - Pullen, Amy; Kieser, D C; Hooper, G
Abstract : Introduction: A review of ballistic gelatin calibration standards has highlighted that data used from studies with different calibrations methods may not be able to be compared. Calibration of ballistic gelatin did not occur until the mid-1980s when Fackler recognised the deficiencies of uncalibrated gelatin. He determined that the calibration standard should be 85±5 mm of ball bearing penetration for a 180 m/s impact velocity. This study looks to improve on and optimise current ballistic gelatin calibration standards Methods: Nine 0.177 cal (4.5 mm) spheres were fired using a Daisy Powerline air rifle at velocities between 134 m/s and 224 m/s at 25 gelatin blocks (n=225). Velocities were measured using an Oehler Model 36 Chronograph with three Model 57 screens. Depth of penetration (DoP) was measured from the entry surface to the back end of the sphere via a Mitutoyo Absolute vernier calliper. Results: The R-squared regression model showed that all batches had a close fit to the regression line. Using the R-squared regression model, the equation y=0.584x – 20.02 (where x is the velocity) returned a DoP of 84.918 mm for a 180 m/s impact and therefore needed minimal adjustment to align with Fackler's 85 mm DoP. The equation can be adjusted to y=0.584x – 20.12 to return a DoP of 85 mm for 180 m/s. Conclusions: We propose that the calibration standard of ballistic gelatin with 4.5 mm spheres is DoP=0.584x – 20.12 where DoP is the depth of penetration (mm) and x is the impact velocity (m/s), The measured DoP should be within 5% of the calculated DoP.